Numerical solution of a space fractional order solute transport system - Jaiswal S.; Chopra M.; Das S. (My University, 2025)
In the present article a drive is taken to compute the solution of spatial fractional order advection-dispersion equation having a source/sink term with given initial and boundary conditions. The equation is converted to a system of ordinary differential equations using second-kind shifted Chebyshev polynomials, which are finally solved using the finite difference method. The striking feature of the article is the fast transportation of solute concentration as and when the system approaches fractional order from standard order for specified values of the parameters of the system. © 2018 by Begell House, Inc.